2003
DOI: 10.1099/mic.0.26126-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic FtsZ polymerization is sensitive to the GTP to GDP ratio and can be maintained at steady state using a GTP-regeneration system

Abstract: In vitro polymerization of the essential bacterial cell division protein FtsZ, in the presence of GTP, is rapid and transient due to its efficient binding and hydrolysis of GTP. In contrast, the in vivo polymeric FtsZ structure which drives cell division -the Z-ring -is present in cells for extended periods of time whilst undergoing constant turnover of FtsZ. It is demonstrated that dynamic polymerization of Escherichia coli FtsZ in vitro is sensitive to the ratio of GTP to GDP concentration. Increase of GDP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…These techniques in combination provide information about the size of FtsZ protofilaments (8) and have been used previously to study other FtsZ inhibitors (21). For these experiments, a stable high GTP/ GDP ratio was achieved by the use of an enzymatic GTP regeneration system (6).…”
Section: Kil Peptide Disrupts Ftsz Protofilaments Triggered By Gtp Lementioning
confidence: 99%
“…These techniques in combination provide information about the size of FtsZ protofilaments (8) and have been used previously to study other FtsZ inhibitors (21). For these experiments, a stable high GTP/ GDP ratio was achieved by the use of an enzymatic GTP regeneration system (6).…”
Section: Kil Peptide Disrupts Ftsz Protofilaments Triggered By Gtp Lementioning
confidence: 99%
“…Assembly-GDP-bound FtsZ polymers have been found to be comparatively unstable compared with the GTP-bound polymers (38,39). Because the GTP hydrolysis rate of the mutant FtsZ was found to be slower than the WT-FtsZ, it is logical to think that under GTP-challenged conditions, E93R-FtsZ polymers would disassemble at a rate slower than that of the WT-FtsZ.…”
Section: E93r Mutation Increased the Steady State Duration Of Ftszmentioning
confidence: 99%
“…The FtsZ9124 protein was expressed from pKD126-9124, as previously described for wild-type FtsZ (41,52). FtsZ6460 was expressed by induction of a culture of BL21(DE3)/pLysS containing plasmid pT73Z-6460 at an A 600 of 0.3 with 0.5 mM isopropyl-␤-Dthiogalactopyranoside (IPTG) for 2 h. FtsZ9124 was initially purified as previously described for wild-type FtsZ protein (52). It was found that a substantial amount of the FtsZ9124 protein was lost during the 20% ammonium sulfate precipitation step; therefore, a second preparation in which the 20% ammonium sulfate precipitate was not discarded was produced.…”
Section: Methodsmentioning
confidence: 99%
“…Negative-stain electron microscopy was performed as described previously (52). Samples were taken from polymerization reaction mixtures before and 1 and 10 min after GTP addition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation